Honey as a Functional Food; Its Culinary Status - Hakan Güleç; Fulya Sarper (Turkish Journal of Agriculture: Food Science and Technology)
Using functional foods which are recently a rising value in the food science arouses curiosity in terms of health among people. Honey, as a natural functional food, might play an important role in the increase of this value with a large but conscious use of it in kitchens. Having a prebiotic property with its oligosaccharide components, honey has a characteristic of supporting the increase of probiotic Bifidobacterium and lactobacilli bacteria. In the current study, the culinary status of honey was investigated depending on the views of professional chef trainers. For honey that shows different compositions, chefs point out that, because of the changes of nectars in the flora collected by bees, the qualitative honey bought from local producers could be a more functional food by using it with sauces, milk products like yoghurt and cheese, with such spices as ginger, turmeric, black pepper, and cinnamon at room temperature without an application of heat treatment.